Prevalence of nasopharyngeal carriage of Streptococcus pneumoniae in children 7 to 14 years in 2016: A survey before pneumococcal conjugate vaccine introduction in Iran - Manoochehr Karami; Seyed Mehdi Hosseini; Seyyed Hamid Hashemi; Sima Ghiasvand; Omid Zarei; Nasim Safari; Hossein Erfani; Mohammad Yousef Alikhani (Taylor & Francis Group, 2019)
Streptococcus pneumoniae is a common cause of community-acquired pneumonia, meningitis, and otitis media in children. The aim of this study was to determine the prevalence of nasopharyngeal carriage of Streptococcus pneumoniae among children in the city of Hamadan, west of Iran. In this cross-sectional study, 532 students aged 7 to 14 years old from Hamadan were enrolled during the period from February to April 2016. Children were recruited using multi-stage sampling method. Informed consent form was obtained from parents of children. A researcher developed checklist was completed for every child by interviewer and samples of the throat of children were taken by swap method from the nasopharyngeal area. Descriptive statistics and chi square test were used to describe the study population. This study was approved by the Committee on Ethics of Hamadan University of Medical Sciences (IR.UMSHA.REC.1394.66). Prevalence of nasopharyngeal carriage of S. pneumoniae in children was 12.03% (95%CI: 9.38-15.10). About 37% (196 persons) of study population were male and 63% were female. Sixty four percent (345 people) of the studied population were from district two in Hamadan and others from District one. Prevalence of nasopharyngeal carriage of S. pneumoniae by sex was 13.77% (95% CI: 9.27-19.40) in males and 11.02 % (95% CI: 7.87-14.85) in females (P = 0.345). Considering the high prevalence of nasopharyngeal carriage of Streptococcus pneumoniae in children studied in Hamadan, pneumococcal conjugate vaccine (PCV) is recommended to be integrated into the Iran's National Immunization Program.